Performance Evaluation of Citizenship Education Teachersin Strengthening Responsible Character in Students at Pelangi Primary School - Saragi, Emi Juwita; Nurbulan, Eka; Rangkuti, Anwar; Yus, Anita; Lubis, Wildansyah (Budapest International Research and Critics University, 2024)
This research aims to explore in depth how the performance evaluation of Pelangi Elementary School Civics teachers influences the strengthening of the character of responsibility in students, by adding qualitative research methods. Qualitative research methods were used to gain deeper insight into the experiences and perceptions of teachers and students related to Civics learning and the formation of responsible character. Through qualitative data analysis, this research identifies effective strategies in improving the quality of Civics learning and forming responsible characters in Pelangi Elementary School students. Evaluation of Civics teacher performance includes the teacher's ability to deliver material, interaction with students, and contribution to school development. Strategies for strengthening responsible character include problem-based learning approaches, discussions and debates, positive behavior models, use of technology and media, and extracurricular activities. It is hoped that the results of this research can provide a valuable contribution to the development of citizenship education and character formation of Pelangi Elementary School students.